2018
DOI: 10.15244/pjoes/85220
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Macrophyte Species Richness in Unmodified and Altered Watercourses

Abstract: Rivers flowing through valleys constitute one of the most diversified ecological systems with one of the highest indexes of biological production, species variety, and abundance of living organisms. Simultaneously, they are frequently subjected to strong anthropogenic activity [1, 2]. Each and every form of interference of a watercourse's stream bed has an effect on its biocoenosis [3, 4]. Regulatory works such as channel resectioning, bank reprofiling, channel deepening, channel widening, and the protection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…As HQA increased, MIR increased as well. These results are like other studies showing the importance of conductivity and hydromorphological conditions to macrophytes [38]. The cumulative frequency distributions of the importance ratios for the dependent variables for MIR (Figure 1b) showed that conductivity had a negative importance ratio for all observed values, indicating its negative correlation with MIR.…”
Section: Resultssupporting
confidence: 88%
“…As HQA increased, MIR increased as well. These results are like other studies showing the importance of conductivity and hydromorphological conditions to macrophytes [38]. The cumulative frequency distributions of the importance ratios for the dependent variables for MIR (Figure 1b) showed that conductivity had a negative importance ratio for all observed values, indicating its negative correlation with MIR.…”
Section: Resultssupporting
confidence: 88%
“…However, when looking at single river stretches, Szoszkiewicz et al (2014) found a significant effect of river width and water depth on species richness of aquatic macrophytes. In temperate small and intermediate-sized lowland streams, channel width also strongly affected plant species richness (Hachol et al, 2019). Modelling river plants, Gillard et al (2020) also found that river width was one of the main drivers of the distributions of different species.…”
Section: Species-area Relationshipmentioning
confidence: 97%
“…In order to validate the results of the analyses, they were compared with the results of previous studies carried out by the authors. For this, 45 transformed study sections described in [67], excluding the sections being the basis of this paper, were analyzed. Figure 6 shows the average, minimum, and maximum values of the number of aquatic plant species in sections where two to six elements in the riverbed were transformed.…”
Section: Figure 3 Andmentioning
confidence: 99%